Диаграмма направленности антенной решетки при сканировании по методу SAFT - Квасников К. Г. Константин Григорьевич; Макаров В. С. Виктор Степанович; Солдатов А. И. Алексей Иванович; Сорокин П. В. Павел Владимирович; Солдатов А. А. Андрей Алексеевич; Крёнинг Х. М. В. А. Ханс Михаэль Вильхельм (Вильгельм) Адольф; Рябушкин А. П. (2012, 2012)
Заглавие с экрана